Array type miniaturized ultrasonic sensors to detect urban sinkholes. (July 2019) - Choi, Won Young; Park, Kwan Kyu
Graphical abstract: Highlights: Detecting sinkhole consist of air medium with the thin thickness of 5 cm asphalt. Implementing linear type ultrasonic transducer array for pulse-echo imaging. Comparison with experimental and simulated 20-dB image result of asphalt – (air or clay) media. Abstract: We present an implementation of a compact sensor system based on an ultrasonic pulse-echo method to detect urban sinkholes in advance. Road depression is caused by damages of artificial structures buried underground such as drain pipes. Previous works on sinkhole detection have been performed variously based on electromagnetic, seismic and resistivity. However, there are technical difficulties such as obtaining a high-resolution image in shallow depth, and implementing a compact surveying device. The goal of this work is to fabricate a miniaturized sinkhole detection system based on low cost ultrasonic transducers with a resonant frequency of 40 kHz, and detect near-ground range. Motivated by biomedical ultrasonic imaging methods, we detected air layers below the asphalt using the pulse-echo method. To improve multi-channel image quality, a linear array system was implemented and images were acquired by classical synthetic aperture imaging for laboratory case study. Feasibility tests of the multi-channel sinkhole detector based on an ultrasonic transducer were successful. We present and analyze images obtained by demonstrating an asphalt model which is working under laboratory conditions and simulations Finite Element Analysis (FEA).